2020
DOI: 10.3390/antiox9010083
|View full text |Cite
|
Sign up to set email alerts
|

Cytoprotective Effects of Delphinidin for Human Chondrocytes against Oxidative Stress through Activation of Autophagy

Abstract: Antioxidant enzymes are decreased in osteoarthritis (OA) patients, implying the role of oxidative stress in osteoarthritis pathogenesis. The aim of this study was to evaluate the cytoprotective effects of delphinidin, a potent antioxidant, in human chondrocytes and the underlying mechanisms. The cytoprotective mechanism induced by delphinidin against oxidative stress (H2O2) in human chondrocytes was investigated. Cell viability and death were evaluated using proapoptotic and antiapoptotic markers such as cleav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 73 publications
1
30
0
Order By: Relevance
“…Due to their antioxidant potential, delphinidin glucosides showed the strongest scavenging activity against superoxide anion and peroxynitrite among several anthocyanins [ 32 ]. Moreover, delphinidin was reported to exert cytoprotective effects for human chondrocytes against oxidative stress [ 33 ], as well as inhibitory effects on oxidative stress in HepG2 cells [ 34 ]. To the best of our knowledge, this is the first study reporting malvidin-3-O-glucoside in A. unedo wild fruit extracts.…”
Section: Resultsmentioning
confidence: 99%
“…Due to their antioxidant potential, delphinidin glucosides showed the strongest scavenging activity against superoxide anion and peroxynitrite among several anthocyanins [ 32 ]. Moreover, delphinidin was reported to exert cytoprotective effects for human chondrocytes against oxidative stress [ 33 ], as well as inhibitory effects on oxidative stress in HepG2 cells [ 34 ]. To the best of our knowledge, this is the first study reporting malvidin-3-O-glucoside in A. unedo wild fruit extracts.…”
Section: Resultsmentioning
confidence: 99%
“…Antioxidants such as α-tocopherol and delphinidin induced autophagy by antioxidant activities [ 83 , 87 ]. α-tocopherol stimulated autophagy and reduced desmin aggregation, determined by increased levels of LC3B-II, in muscle cells [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…Delphinidin inhibited ROS-induced apoptosis and induced autophagy. Autophagy was assessed by the formation of LC3B-II and autophagosomes (LC3B puncta and AO staining) in human chondrocytes [ 87 ]. Therefore, antioxidant compounds may increase the number of AO-positive cells and LC3B puncta.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, delphinidin could inhibit the proliferation of SKOV3 cells (ovarian cancer cells) [ 26 ] and it could prevent prostate cancer via inhibiting the apoptosis mediated by p53 [ 27 ]. Lee et al reported that delphinidin could protect chondrocytes against H 2 O 2 -mediated oxidative stress by activating NF- κ B and Nrf2 [ 28 ]. However, there is a lack of data on how delphinidin regulates Nrf2 to exert the function of antioxidant stress.…”
Section: Introductionmentioning
confidence: 99%